Risk Factors for Anterior Tibial Tendon Pathology. (March 2021) - Levitsky, Matthew M.; Freibott, Christina E.; Greisberg, Justin K.; Vosseller, J. Turner
Background: Though the tibialis anterior (TA) serves a vital role in ankle dorsiflexion, there is little information regarding risk factors and demographic information that might predispose one to tendinopathy or rupture. This study investigates the features of patients in a single institution who presented with either TA tendinopathy or rupture. The circumstances surrounding rupture were also noted. Methods: ICD-9/10 codes were used to find patients who presented with TA pathology to 2 foot and ankle surgeons at 1 academic medical center from 2011 to 2018. Patient characteristics were noted, including age, sex, body mass index, and the presence of a gastrocnemius equinus contracture. Characteristics of patients with traumatic and atraumatic ruptures were compared. Results: Ninety-four patients presented between 2011 and 2018 (79 cases of tendinopathy and 15 ruptures). The average patient age was 56 years, and the ratio of women to men was 74:20 (3.7:1). With regard to those who experienced rupture, there were 2 ruptures directly related to athletic activity (traumatic), whereas 13 ruptures were found on examination with no overt history of injury (atraumatic). The average age for patients with traumatic ruptures was 39 years compared with 73 years for those with atraumatic rupture ( P < .05). Conclusion: This study investigates the features of patients in a single institution who presented with TA pathology. With regard to tendon ruptures, traumatic ruptures tend to occur in younger patients, whereas older patients are more likely to suffer atraumatic ruptures. Nonoperative treatment often appears to be effective for TA pathology. Level of Evidence: Level III, retrospective comparative series.